Pengembangan Buku Panduan Anti-Bullying untuk Mengembangkan Keterampilan Sosial-Emosional Anak Usia Dini - Agustin Ningrum, Mallevi; Mahendra R. K. Wardhani, Andhea (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The incidence of bullying that often occurs among teenagers and adults has begun to spread among early childhood. Lack of knowledge about bullying sometimes makes teachers and parents ignore things that can lead to bullying. The purpose of this study was to produce a product in the form of a guidebook for anti-bullying activities for children aged 5-6 years for proper and effective Early Childhood Education (ECE) teachers. This research includes Research and Development model ADDIE (Analyze, Design, Development, Implementation and Evaluate). The data collection technique in this study used an online questionnaire in a google form which was distributed to 40 ECE teachers. The results of the study show that 1) The guidebook “Anti-Bullying” is suitable for use and meets the material feasibility score of 80.5% in the valid category and the media feasibility 87.5% with the very valid category; 2) The trial results show that the guidebook is very effective to use for ECE teachers with a percentage of 88.1%. The findings of this study contribute in the form of understanding and input to policymakers to make this book the main reference for bullying prevention in early childhood.